Magnetocrystalline anisotropy study of Co-substituted M-type strontium hexaferrite single crystals. Issue 2 (15th January 2023) - Liu, Ruoshui; Wang, Lichen; Yu, Xiang; Xu, Zhiyi; Gong, Huayang; Zhao, Tongyun; Hu, Fengxia; Shen, Baogen
Abstract: The study on the magnetocrystalline anisotropy (MA) of La–Co co-substituted strontium hexaferrite (La–Co SrM) shows a joint effect of Fe 2+ and Co 2+ ions in the enhancement of MA. Since the role of Fe 2+ single ion has been studied with La-substituted strontium ferrite, in this work, Co-substituted strontium hexaferrite SrFe12- x Co x O19 (Co-SrM) single crystals were successfully grown for 0 ≤ x ≤ 0.31 by the Na2 CO3 flux method to elucidate the anisotropy of Co 2+ single ions. Co-substitution in this preparation condition has a limit solubility of 0.31 and enhances uniaxial magnetic anisotropy field H A by 19% for 0.03 = x ≤ 0.11, with a mere loss of 7% of saturation magnetization M S at 5 K. The enhanced H A of Co-SrM is reported for the first time, even higher than that of La–Co SrM, which is suitable to be used as permanent magnets in this concentration range. But with the further substitution of Co, the planar anisotropy of x = 0.31 was observed at 5 K. The potential nonlinear magnetic structure of Co-SrM remains to be discovered for magnetoelectric effects. This work is also of great significance as a complement to the magnetocrystalline anisotropy study of La–Co SrM.